Early prediction of acute kidney injury in patients with gastrointestinal bleeding admitted to the intensive care unit based on extreme gradient boosting - Shi, Huanhuan; Shen, Yuting; Li, Lu (Frontiers in Medicine, 2023)
Background: Acute kidney injury is a common and important complication in patients with gastrointestinal bleeding who are admitted to the intensive care unit. The present study proposes an artificial intelligence solution for Acute kidney injury prediction in patients with gastrointestinal bleeding admitted to the intensive care unit. Methods: Data were collected from the eICU Collaborative Research Database (eICU-CRD) and Medical Information Mart for Intensive Care-IV (MIMIC-IV) database. The prediction model was developed using the extreme gradient boosting (XGBoost) model. The area under the receiver operating characteristic curve, accuracy, precision, area under the precision-recall curve (AUC-PR) and F1 score were used to evaluate the predictive performance of each model. Results: Logistic regression, XGBoost, and XGBoost with severity scores were used to predict acute kidney injury risk using all features. The XGboost based acute kidney 2 injury predictive models including XGboost and XGboost+severity scores model showed greater accuracy, recall, precision AUC, AUC-PR and F1 score compared to logistic regression. Conclusion: The XGBoost model obtained better risk prediction for acute kidney injury in patients with gastrointestinal bleeding admitted to the intensive care unit than the traditional logistic regression model, suggesting that machine learning techniques have the potential to improve the development and validation of predictive models in patients with gastrointestinal bleeding admitted to the intensive care unit.